Cyber-thief showdown - Stilton, Geronimo; Dami, Elisabetta (Geronimo Stilton, 2018)
When he begins receiving packages containing useless things he did not order, Geronimo Stilton discovers that someone on the Internet has stolen his identity, a dilemma that compels him to enlist the help of computer expert Professor Margo Bitmouse, who helps Geronimo track down the hacker.